Follow-up evaluation of children with birth weight less than or equal to 2,000 g - Freitas, Marcia de; Siqueira, Arnaldo; Segre, Conceição Aparecida de Mattos (São Paulo Medical Journal, 2004)
CONTEXT: During the first year of life, the growth process is highly vulnerable to several impairing factors that need to be understood. OBJECTIVE: To perform follow-up evaluation on newborns weighing less than or equal to 2,000 g in a population of low socioeconomic level. TYPE OF STUDY: Retrospective. SETTING: Hospital Maternidade Escola de Vila Nova Cachoeirinha, São Paulo, Brazil. METHODS: The study included 60 children born between March 1996 and January 1998, weighing less than or equal to 2,000 g. They were divided into three subgroups, according to birth weight and adequacy for gestational age. The factors studied were maternal variables, illnesses among the newborns, hospital admissions subsequent to discharge from the nursery, and the evolution of weight from birth until 12 months of life. Statistical analyses were performed through application of the Statistical Package for Social Sciences (SPSS) V.9.0 and Curve Expert 1.3 programs. RESULTS: Previous maternal diseases occurred in 38.6% of the pregnant women and intercurrent events occurred in 100%. The prevailing neonatal diseases were sepsis (30%) and hyaline membrane disease (25%). There were 404 visits on an outpatient basis: the most frequently diagnosed complaints related to respiratory diseases (26%). Among visits to specialists, 81.7% were to the neuropediatrician. A diagnosis of normality was made for 80% of all visits, for all specialties. For each of these groups, a growth curve was established. These were shown to be below the reference curve standards, with such differences least evident with regard to the children’s corrected age. DISCUSSION: The severity of the newborns’conditions may be related to the high incidence of maternal diseases prior to pregnancy as well as intercurrent events during pregnancy. The differences in growth in relation to NCHS charts show that corrected age should be used as a parameter. CONCLUSIONS: Socioeconomic conditions, clinical/ obstetric events and newborn diseases during the hospital stay had repercussions on these children’s progress during their first year of life. Their growth profile was found to be very far from the reference standard, thus indicating a need for constant, differentiated assessment.